Neuron-Specific Fluorescence Reporter-Based Live Cell Tracing for Transdifferentiation of Mesenchymal Stem Cells into Neurons by Chemical Compound - Do Won Hwang; Hyun Woo Kwon; Jaeho Jang; Hee Jung Jung; Kwang Rok Kim; Dong Soo Lee (Hindawi Limited, 2017)
Although transdifferentiation of mesenchymal stem cells (MSCs) into neurons increases the possibility of therapeutic use of MSCs for neurodevelopmental disorders, the use of MSCs has the limitation on differentiation efficiency to neuronal lineage and lack of an easy method to monitor the transdifferentiation. In this study, using time-lapse live cell imaging, we assessed the neuronal differentiation of MSCs induced by a small molecule "NHPDQC (N-hydroxy-2-oxo-3-(3-phenylprophyl)-1,2-dihydroquinoxaline-6-carboxamide, C18H17N3O3)." Plasmid vector containing red fluorescence reporter genes under the control of the tubulin α1 (Tα1) promoter (pTα1-DsRed2) traced the neuronal differentiation of MSCs. Two days after NHPDQC treatment, MSCs showed neuron-like phenotype with neurite outgrowth and high expression of neuron-specific markers in more than 95% cells. The fluorescence signals increased in the cytoplasm of pTα1-DsRed2-transfected MSCs after NHPDQC treatment. In vitro monitoring of MSCs along the time courses showed progressive increase of fluorescence till 30 h after treatment, corresponding with the increase in neurite length. We examined an efficient neuronal differentiation of MSCs by NHPDQC alone and monitored the temporal changes of neuronal differentiation by neuron-specific fluorescence reporter along time. This method would help further our understanding of the differentiation of MSCs to produce neurons by simple treatment of small molecule.